Akuntansi untuk Dana Pensiun - Permatasari, Intan (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2023)
ABSTRACT The purpose of this research is to explain pension fund accounting and find out the purpose of reporting PPIP pensions. This research method uses qualitative methods to explain objects clearly, data sources come from literature studies. Based on the results of this study, pension fund reporting by PPMP organizers periodically provides information on pension program administration, financial condition and investment returns, which are useful for determining pension fund wealth according to the size. of payment obligations.